Guide to Modeling and Simulation of Systems of Systems - Zeigler, Bernard P. (Simulation Foundations, Methods and Applications,, 2013)
Systems of systems are at the root of this centurys global challenges of economy, climate, and energy. Building and testing such systems within a virtual reality is the only workable alternative when direct real-world experimentation is potentially dangerous, costly or unethical. This Guide to Modeling and Simulation of Systems of Systems demonstrates how virtual build and test can be supported by the Discrete Event Systems Specification (DEVS) simulation modeling formalism, and the System Entity Structure (SES) simulation model ontology. The book examines a wide variety of Systems of Systems (SoS) problems, ranging from cloud computing systems to biological systems in agricultural food crops. Topics and features: Includes numerous exercises, examples and case studies throughout the text, together with introductory and summary sections Discusses how the SoS concept and supporting virtual build and test environments can overcome the limitations of current approaches Presents a step-by-step introduction to DEVS concepts, encouraging hands-on practice to building sophisticated SoS models Illustrates virtual build and test for a variety of SoS applications using DEVS simulation environments: MS4 Me", CoSMoS/DEVS-Suite and Virtual Laboratory Environment Examines a range of diverse applications, from the development of new satellite design and launch technologies, to surveillance and control in animal epidemiology Introduces an approach based on activity concepts intrinsic to DEVS-based system design, that integrates both energy and information processing requirements Describes co-design modeling concepts and methods to capture separate and integrated software and hardware systems This exercise-driven and easy-to-follow guide/reference is an essential practical resource for graduate students and instructors.